Оptimization of Treatment EBV Infectious Mononucleosis in Children - V. B. Kotlova (Detskie Infekcii (Moskva), 2015)
The paper presents the results of observation of 103 children aged from 10 months to 15 years with EBV-associated infectious mononucleosis (IM), determined in 32% by acute primary Epstein-Barr virus infection (AEBVI) and in 68% of cases by reactivation of chronic Epstein-Barr virus infection (CEBVI). Clinical and laboratory characteristics of the course, depending on the form of infection, were investigated. As a clinical outcome of infectious mononucleosis in patients with primary infection latent infection after a year is formed 5.8 times more often than in patients with chronic Epstein-Barr virus infection (CEBVI). The high efficiency of recombinant interferon monotherapy in patients with primary acute infection was recorded and the expediency of combined etiotropic therapy in the treatment of chronic Epstein-Barr virus infection was found out.